KEMAMPUAN MENYELESAIKAN SOAL MATA KULIAH STATISTIK EKONOMI II - Zainur Hidayah; Lely Fera Triani (LPPM Universitas Terbuka, 2007)
Long-distance learning system has been known in Indonesia far before UT was establised in 1984. The questioning differences between long-distance learning system and conventional system still persist until today. This question is co-related with the doubt of how to implement the long-distance learning system with very large number of students across the nations who are far from the source of learning, and with ununified compentency of the program input. This research is using non-parametric statistics to identify differences of student ability between UT students, X University students, and Y University students, in answering essays of Economic Statistics II measured in 2 categories: comparing question patterns and test results done by students from different universities. For the face-to-face or conventional system, this study use two different institution, X university and Z university, so the comparisons can be done twice to two a different and the same systems. There are 49 respondents that consists of 20 undergraduate students of X university, 19 undergraduate students of Y university, and 10 undergraduate students of UT. The data collected will be analyzed using non-parametric statistics, the Chi-Square Method. From the testing process standpoint, there is no significant difference among students of UT, University X, and Unversity Y. And also between students university X and unversity Y. From the testing result standpoint, students of UT, University X, and Unversity Y show relatively the same result with a degree 95%